Crystal structure of a ligand-free stable TSH receptor leucine-rich repeat domain. (April 2019) - Miller-Gallacher, Jennifer; Sanders, Paul; Young, Stuart; Sullivan, Andrew; Baker, Stuart; Reddington, Samuel C; Clue, Matthew; Kabelis, Katarzyna; Clark, Jill; Wilmot, Jane; Thomas, Daniel; Chlebowska, Monika; et al.
Abstract : The crystal structures of the thyroid-stimulating hormone receptor (TSHR) leucine-rich repeat domain (amino acids 22–260; TSHR260) in complex with a stimulating human monoclonal autoantibody (M22 TM ) and in complex with a blocking human autoantibody (K1-70™) have been solved. However, attempts to purify and crystallise free TSHR260, that is not bound to an autoantibody, have been unsuccessful due to the poor stability of free TSHR260. We now describe a TSHR260 mutant that has been stabilised by the introduction of six mutations (H63C, R112P, D143P, D151E, V169R and I253R) to form TSHR260-JMG55 TM, which is approximately 900 times more thermostable than wild-type TSHR260. These six mutations did not affect the binding of human TSHR monoclonal autoantibodies or patient serum TSHR autoantibodies to the TSHR260. Furthermore, the response of full-length TSHR to stimulation by TSH or human TSHR monoclonal autoantibodies was not affected by the six mutations. Thermostable TSHR260-JMG55 TM has been purified and crystallised without ligand and the structure solved at 2.83 Å resolution. This is the first reported structure of a glycoprotein hormone receptor crystallised without ligand. The unbound TSHR260-JMG55 TM structure and the M22 and K1-70 bound TSHR260 structures are remarkably similar except for small changes in side chain conformations. This suggests that neither the mutations nor the binding of M22 TM or K1-70 TM change the rigid leucine-rich repeat domain structure of TSHR260. The solved TSHR260-JMG55 TM structure provides a rationale as to why the six mutations have a thermostabilising effect and provides helpful guidelines for thermostabilisation strategies of other soluble protein domains.